2018
DOI: 10.18805/ijar.b-911
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Bovine papillomavirus-induced teat warts in a cow by using Podophyllin magistral formula and autologous vaccine applications together

Abstract: In this study, a 32-month-old Holstein cow that had a calving and common Bovine papillomavirus (BPV)-induced wart on its teats was treated. For this purpose, BPV antigen presence in blood serum sample from the animal was studied by ELISA and was revealed as positive. Magistral drug containing podophyllin active substance was applied topically on teat warts of the animal. Applications were performed for all teat warts once in three days during 27 days. Eight hours after applying the drug, teats were washed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Udder myiasis was treated successfully with complete recovery, which was similar with the treatment procedures of Rahman et al (2009). The uses of autogenous vaccine for udder and teat papilloma (wart) were effective and corresponding to the researches of Khalid et al (2021), Nethra and Babu (2018) and Kale et al (2019). The management procedures of teat canal polyps, superficial teat cracks and teat sores were feasible to bring positive outcomes in terms of morphology and function of mammary tissue, and were collateral as described by Rathod et al (2009), Nouh et al (2014), Khan et al (2020) and Sharma et al (2020).…”
Section: Discussionmentioning
confidence: 58%
“…Udder myiasis was treated successfully with complete recovery, which was similar with the treatment procedures of Rahman et al (2009). The uses of autogenous vaccine for udder and teat papilloma (wart) were effective and corresponding to the researches of Khalid et al (2021), Nethra and Babu (2018) and Kale et al (2019). The management procedures of teat canal polyps, superficial teat cracks and teat sores were feasible to bring positive outcomes in terms of morphology and function of mammary tissue, and were collateral as described by Rathod et al (2009), Nouh et al (2014), Khan et al (2020) and Sharma et al (2020).…”
Section: Discussionmentioning
confidence: 58%
“…In their research, they found a favorable result. A dairy cow with severe teat warts was treated by Kale et al (2019) using podophyllin and an autologous vaccination. They used ELISA to check for the presence of BPV (Ag) in the animal's blood serum and found a positive result.…”
Section: Discussionmentioning
confidence: 99%
“…Los métodos quirúrgicos (electrocauterio, ligadura y crioterapia) (23), homeopatía, farmacoterapia inmunomoduladora y antibioterapia (24,25,26), inyecciones químicas como tiomalato de litio y antimonio (26), autovacunación y autohemoterapia son algunos de estos métodos. (23,27).…”
Section: Introductionunclassified